Exposure of Mice to 1, 2-Dichloropropane Induces CYP450-Dependent Proliferation and Apoptosis of Cholangiocytes. (7th December 2017) - Zhang, Xiao; Zong, Cai; Zhang, Lingyi; Garner, Edwin; Sugie, Shigeyuki; Huang, Chinyen; Wu, Wenting; Chang, Jie; Sakurai, Toshihiro; Kato, Masashi; Ichihara, Sahoko; Kumagai, Shinji; et al.
Abstract: 1, 2-Dichloropropane (1, 2-DCP) has been used as a paint remover in the industry. The International Agency for Research on Cancer reclassified this compound recently to group 1 (carcinogenic to humans) based on epidemiological studies of cholangiocarcinoma among offset-color proof-printing workers exposed to 1, 2-DCP in Japan. Two-year rodent carcinogenicity bioassays demonstrated that 1, 2-DCP induced tumors in liver and lung, but not in bile duct. The present study was designed to assess the toxic effects of 1, 2-DCP on proliferation and apoptosis in mice bile duct and the role of cytochrome P450 (CYP450) in any such effect. Male C57BL/6JJcl mice were cotreated or untreated with 1-aminobenzotriazole (1-ABT), a CYP450 inhibitor, and exposed to inhalation of 1, 2-DCP at 0, 50, or 250 ppm alone, or at 0, 50, 250, or 1250 ppm 8 h/day for 4 weeks. Exposure to 1, 2-DCP increased proliferation and apoptosis of cholangiocytes and induced severe hepatic damage, but had no effect on the lungs. Cotreatment with 1-ABT abrogated the effects of 1, 2-DCP on proliferation and apoptosis of cholangiocytes. The results revealed that 1, 2-DCP induces proliferation and apoptosis of cholangiocytes and that this effect is mediated through CYP450.